Manajemen Talenta di Pemerintah Daerah: Studi Eksplaratori Penerapan Kebijakan Manajemen Talenta di Provinsi Kalimantan Timur dan Kalimantan Utara: Talent Management in Local Government: An Explaratory Study of The Implementation of Talent Management Policy in East Borneo and North Borneo Provinces - Suparman, Rahmat; Naibaho, Veronika Hanna (Pusjar SKPP Lembaga Administrasi Negara, 2021)
The study of talent management (TM) in local governments is still rare and less popular than research on similar practices in business organizations. However, this condition will soon change with the issuance of a policy on the implementation of talent management in 2020 issued by the Ministry of Administrative Empowerment (PAN) and Bureaucratic Reform (RB). This article aims at exploring to what extent the readiness of the HRM agencies at East Borneo and North Borneo province in implementing the current talent management policy. Using exploitative-qualitative methods through interviews with senior officials of regional staffing agencies, this article discusses policy understanding, institutional capacity, and regional head support in the implementation of TM. The results of the analysis showed that the understanding of TM policy by stakeholders is sufficient with the implementation plan in line with the established policy. Furthermore, the TM implementation approach in both regions is more dominant using a strategic-system approach than micro-individualistic, both at the stage of selecting employees, with talent criteria consisting of potential, performance, competence, and ethics-integrity, and the provision of competency development programs adjusted to the needs of talents. This research also showed that with the institutional capacity of different human resources managers in both provinces, East Kalimantan province is relatively more ready to implement TM than North Kalimantan province. However, the toughest challenge of the implementation in both provinces is to get the support of regional heads so that the process of implementing talent management can run effectively, without transactional political intervention. Studi tentang manajemen talenta (MT) di organisasi publik masih jarang dilakukan dibandingkan dengan penelitian sejenis di organisasi bisnis. Namun, kondisi ini akan segera berubah seiring terbitnya kebijakan penerapan manajemen talenta pada Tahun 2020 yang dikeluarkan Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi (PAN RB). Artikel ini ingin menjawab pertanyaan tentang sejauh mana kesiapan instansi pengelola SDM di Provinsi Kalimantan Timur dan Kalimantan Utara untuk menerapkan kebijakan manajemen talenta. Menggunakan metode eksploratori-kualitatif melalui wawancara dengan pejabat senior badan kepegawaian daerah, artikel ini membahas pemahaman kebijakan, kapasitas kelembagaan, dan dukungan kepala daerah dalam penerapan MT. Hasil analisis menunjukkan bahwa pemahaman tentang kebijakan MT oleh pemangku kepentingan sudah cukup memadai dengan rencana penerapan yang sesuai dengan kebijakan yang telah ditetapkan. Pendekatan penerapan MT di kedua daerah lebih dominan menggunakan pendekatan system strategis daripada mikroindividualistik, baik pada tahapan menyeleksi pegawai, dengan kriteria talenta yang terdiri dari potensi, kinerja, kompetensi dan etika-integritas, maupun pemberian program pengembangan kompetensi yang disesuaikan dengan kebutuhan talenta. Penelitian ini juga menunjukkan bahwa dengan kapasitas kelembagaan pengelola SDM yang berbeda di kedua provinsi, Provinsi Kalimantan Timur relatif lebih siap menerapkan MT dibandingkan dengan Provinsi Kalimantan Utara. Namun, tantangan terberat penerapan MT di kedua provinsi adalah mendapatkan dukungan kepala daerah agar proses implementasi manajemen talenta dapat berjalan secara efektif, tanpa adanya intervensi politik transaksional.